2023
DOI: 10.22541/au.167364749.93845737/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dependence of fast changes in global and local precipitation on the geographical location of aerosol absorption

Abstract: Anthropogenic aerosol interacts strongly with incoming solar radiation, perturbing the Earth's energy budget and precipitation on both local and global scales. Understanding these changes in precipitation has proven particularly difficult for the case of absorbing aerosol, which absorbs a significant amount of incoming solar radiation and hence acts as a source of localized diabatic heating to the atmosphere. In this work, we use an ensemble of atmosphere-only climate model simulations forced by identical aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Furthermore, the role of other modeling choices, such as horizontal and vertical resolution and the role of boundary conditions (Dagan et al, 2022) in our results should be examined in future work. In addition, in this work we excluded aerosol-radiation interactions, which could drastically alter TOA energy gain (Bellouin et al, 2020;Williams et al, 2023), and as such could be of interest. Finally, our work is based on single-model simulations.…”
Section: Examining the Surface Precipitation Response To Aerosol Pert...mentioning
confidence: 99%
“…Furthermore, the role of other modeling choices, such as horizontal and vertical resolution and the role of boundary conditions (Dagan et al, 2022) in our results should be examined in future work. In addition, in this work we excluded aerosol-radiation interactions, which could drastically alter TOA energy gain (Bellouin et al, 2020;Williams et al, 2023), and as such could be of interest. Finally, our work is based on single-model simulations.…”
Section: Examining the Surface Precipitation Response To Aerosol Pert...mentioning
confidence: 99%
“…These factors warrant further investigation and may refine our understanding of the relationship between absorbing aerosols and extreme precipitation (e.g., see Dagan et al (2023) for large domain simulations of hothouse climate episodic deluges regime). Furthermore, previous studies using global climate simulations (Dagan et al, 2021;Persad, 2023;Williams et al, 2023) demonstrated that the location of the absorbing aerosol perturbation matters for the local-and global-mean precipitation response. Thus, it will also be interesting to examine the response of extreme precipitation to different geographical locations of aerosol perturbation in global convective-resolving simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the intricate processes that govern precipitation is crucial for addressing water resource management, flood risks, and climate change impacts. Recent research has highlighted the significant role of aerosols, particularly absorbing aerosols, in modulating the energy budget of the atmosphere and subsequently influencing precipitation patterns (Dagan et al., 2019; Herbert et al., 2021; Liu et al., 2018; Samset, 2022; Sand et al., 2020; Williams et al., 2023). Absorbing aerosols, such as black carbon (Bond et al., 2013), possess the ability to absorb solar radiation and alter the vertical temperature gradient (Lu et al., 2020; Stjern et al., 2017; Wilcox et al., 2016), thereby perturbing the convective dynamics and thermodynamic conditions conducive to precipitation.…”
Section: Introductionmentioning
confidence: 99%